2020
DOI: 10.3390/electronics9111884
|View full text |Cite
|
Sign up to set email alerts
|

High-Voltage Temperature Humidity Bias Test (HV-THB): Overview of Current Test Methodologies and Reliability Performances

Abstract: The high voltage temperature humidity bias test (HV-THB) has become increasingly popular for evaluating the performances of power semiconductor devices. Given the new challenges of the power semiconductor industry, several applications and devices need to be designed to withstand harsh environments during working operations, with a remarkable focus on high-humidity conditions. The HV-THB test allows one to activate and study different failure mechanisms which were not highlighted by the standard low voltage TH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 48 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…In this case, solutions pass through a proper packaging technology, for instance using organic passivant like GlobTop. Stability and reliability evaluation of the termination can be done using High Temperature Reverse Bias test (HTRB) [12], including Humidity (H3TRB) [13][14], if a proper evaluation of the passivation is to be done. It is also relevant to test the termination under Unclamped Inductive Switching (UIS) to check the avalanche capability of the device [1].…”
Section: Edge Termination Structuresmentioning
confidence: 99%
“…In this case, solutions pass through a proper packaging technology, for instance using organic passivant like GlobTop. Stability and reliability evaluation of the termination can be done using High Temperature Reverse Bias test (HTRB) [12], including Humidity (H3TRB) [13][14], if a proper evaluation of the passivation is to be done. It is also relevant to test the termination under Unclamped Inductive Switching (UIS) to check the avalanche capability of the device [1].…”
Section: Edge Termination Structuresmentioning
confidence: 99%
“…There have also been works focused on accelerated aging due to thermal stresses from thermal power cycling between 25 and 125 • C [10]. S. Song et al observed electrical cracks in the degraded devices, corresponding to increased leakage current, while the threshold voltage and on-state resistance have been unaffected [11]. These works have not included a combination of humidity, high temperature, and blocking voltage in their testing, as they can accelerate power devices' failure mechanisms [12].…”
Section: Introductionmentioning
confidence: 99%